2014
DOI: 10.1016/j.fuel.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of char and soot from millimetric wood particles pyrolysis in a drop tube reactor between 800°C and 1400°C

Abstract: Char and soot characterization was performed for samples obtained from beech particles pyrolysis in a drop tube reactor at various temperatures and residence times. Firstly, an experimental study was per formed and highlights the variation of char and soot composition and reactivity with operating condi tions. A structure ordering with temperature for soot samples was also experimentally put into evidence. These variations are believed to be consequence of structural changes during char thermal annealing and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The XPS spectra of pinewood and beechwood soot mainly exhibit the carbon and oxygen lines with some traces of sodium, whereas herbaceous biomass soot samples additionally showed K 2p and Cl 2p lines, as shown in the supplemental material (Table S- 4). The K and Cl atomic concentrations for the alfalfa straw soot were 3.5 and 1.2 at.%, whereas the K and Cl atomic ratio in pure KCl is 1:1, respectively.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 91%
See 1 more Smart Citation
“…The XPS spectra of pinewood and beechwood soot mainly exhibit the carbon and oxygen lines with some traces of sodium, whereas herbaceous biomass soot samples additionally showed K 2p and Cl 2p lines, as shown in the supplemental material (Table S- 4). The K and Cl atomic concentrations for the alfalfa straw soot were 3.5 and 1.2 at.%, whereas the K and Cl atomic ratio in pure KCl is 1:1, respectively.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 91%
“…The released alkali metal ions in the biomass pyrolysis participate in soot formation and conversion reactions. It is known that alkali metal ions enhance CO 2 reactivity of graphite and carbon black [3] and suppress soot formation [4]. The alkali metal ions can form a fly ash or be bonded to oxygen-containing surface groups in the soot matrix [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…López et al [25] investigated the pyrolysis of four different types of biomass samples in N 2 and observed that the chars produced from oaks had a marked crystalline nature due to CaCO 3 formation while chars derived from silver fir and stone fir did not contain CaCO 3 . Also, in a recent study, the XRD analysis of the pyrolysis chars of beech wood at temperatures higher than 1000 • C in a drop tube furnace also showed the formation of CaCO 3 [26]. Further investigations are needed to understand how the carbonate species were formed, during the pyrolysis in the isothermal high temperature reaction zone of a drop tube furnace or downstream process where temperatures fall dramatically.…”
Section: Characterizationmentioning
confidence: 97%
“…Moreover, soot gasification by steam and CO 2 is neglected. Indeed, soot gasification experiments have shown that soot gasification by steam was 2-20 times slower than char gasification between 750°C and 950°C [27]. Soot gasification by CO 2 is 2-30 times slower than char gasification at 1100°C [28].…”
Section: Char Gasificationmentioning
confidence: 99%